Modelagem de nicho ecológico aplicada à conservação do patomergulhão (Mergus octosetaceus, Vieillot, 1817) no Brasil - Bueno, Bruno Arantes de Andrade (2012)
The Brazilian Merganser (Mergus octosetaceus) is a critically-endangered species whose largest wild populations can be found at conservation units in Brazil. Habitat loss and degradation due to anthropic interference are the main threats to its survival. I used nine different niche modeling algorithms to build a consensus model composed of the best five models to predict Mergus octosetaceus potential geographical distribution in Brazil. I also employed a multicriteria analysis technique (weighted linear combination) in a GIS environment to map anthropic pressure levels over the species potential range. Modeling of the potential geographical distribution resulted in a habitat suitability map which indicated 17.3% of the national territory as suitable to occurrence of M. octosetaceus. Two hundred and nineteen integral protection conservation units were identified as protecting 2.66% of the species potential range. Besides indicating new potential occurrence areas, the habitat suitability map confirmed current and historical occurrence records. Application of the weighted linear combination resulted in a map of three anthropic pressure levels (low, medium, and high), with high level prevailing over 40.8% of M. octosetaceus potential range. Brazilian Merganser s occurrence points tended to be associated with areas of low anthropic pressure, supporting the notion that interference of anthropic factors lead to its exclusion from altered habitats.